Answer:
T(x, y) = (x - 5, y - 6)
Step-by-step explanation:
The transformation T is a translation that creates an image P' of original point P by adding 5 to the x-coordinate and 6 to the y-coordinate of the original point P.
Now you want to transform point P' into point P, so you are undoing the first transformation. You need to do the opposite of what the transformation above does. You need to subtract 5 from the x-coordinate and subtract 6 from the y-coordinate.
Answer: T(x, y) = (x - 5, y - 6)
1.5x will be the very answer
Answer:
36/5
Step-by-step explanation:
x/3 + 6 -2x = -6
multiply the whole equation by 3 to get rid of the denominator of the first x term.
x+18-6x = -18
move x terms to one side and numerical terms to the other, subtract 18 from both sides in this case
x+18-6x-18=-18-18
x-6x = -36
simplify
-5x = -36
divide both sides by -5 to isolate x
x = -36/-5
=36/5
Answer:
942.48
Step-by-step explanation:
V=πr^2h=π·5^2·12≈942.4778
Answer: B (2,1)
You know what y is (x-1) so you substitute that for y in the other equation.
3x+ ((4)(x-1))=10
3x+4x-4=10
7x=14
x=2
Then put x=2 into y=x-1
y=2-1
y=1